Strategi Pemasaran Madrasah Tsanawiyah Babul Hikmah Kedaton Kalianda Lampung Selatan - Aflah Aliyati (An Naba, 2022)
This Thesis is the result of research that describes four marketing strategies including market segmentation, target market, market positioning, and marketing mix that have been implemented by madrasah Tsanawiyah Babul Hikmah. These four strategies have an impact on increasing the number of students starting from the 2018/2019 Academic Year to the 2021/2022 Academic Year.This type of research is qualitative using a narative approach based on case studies. Sourch of data are the Head of Madrasah, Deputy Head of Kurikulum, Head of PSB, Secretary of PSB, and Guardians of Studies. This study uses observation, interview & documentation to colect data. Then the data that has been collected is analyzed using the stages of data reduction, data presentation and drawing conclusions.The results of this study reveal that the four marketing strategies that have been implemented have a good impact on increasing the number of students from year to year, in addition to the four marketing strategies that have been implemented by MTs Babul Hikmah, there are two things that have a stronger impact on public interest and increase the number of students in MTs Babul Hikmah. As for the two things, the first is service, then the second is the relationship that the teacher council of MTs Babul Hikmah establishes to the guardians of the students.